Implementation Of Indonesia's Cooperation With Denmark In Waste Management - Enny Fathurachmi; Andi Purnawarman (LPPPIPublishing, 2022)
Garbage is a problem for every country in this world, including Indonesia that has large population and is related to the amount of garbage in Indonesia. To slove this problem Indonesia goverment need thecnology and good waste management in Indonesia. Denmark has good waste management and thecnology to turn waste become energy, because of that Indonesia coorperates with Denmark in waste management. This study aims to describe the coorperation between the Indonesia and Danish (Denmark) goverment in waste management in DKI Jakarta. The methedodology used is descriptive qualitative through secondary data which then answerd by using international cooperation theory and waste management concept. The results showed that in the collaboration carried out by Indonesia and Denmark, there were 8 points of cooperation but only 2 points were implemented in DKI Jakarta, namely pilot projects, planning, including technology transfer and regulations in certain provinces and cities or regencies, in this point of cooperation Indonesia and Denmark built PLTSa in DKI Jakarta, precisely at TPST Bantargebang, this PLTSa waste management method uses waste and uses steam from its combustion to be used as electricity and capacity building through workshops, training, scholarships, internships and seminars, which are manifested in Information Transfer (ToI) to monitor the waste management system in Indonesia and the efficiency of energy use and utilization, which is carried out in two programs, namely Capacity Building: Training for Jakarta Building and Energy Efficiency Seminar, in this program Denmark aims for Indonesia to conduct Business Par partnerships with partners energy company in Denmark.